2010
DOI: 10.1111/j.1365-2095.2010.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentation and carotenoid content of shrimp fed with Haematococcus pluvialis and soy lecithin

Abstract: The aim of this work was to evaluate the effects of Haematococcus pluvialis (H. pluvialis) (carotenoid source) and H. pluvialis plus soy lecithin on development, carotenoid content, and pigmentation of shrimp (Litopenaeus vannamei). One hundred and eighty shrimps (7.8 g) were divided in six tanks (n = 30) and fed with control food, H. pluvialis, and H. pluvialis plus soy lecithin for 2 weeks. Carotenoids were extracted with acetone and quantified by UV–vis spectrophotometry, and astaxanthin was determined by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 23 publications
4
43
0
1
Order By: Relevance
“…A similar effect was also reported on Kuruma prawn (Penaeus japonicus) fed with -carotene from Dunaliella salina (Supamattayaa et al, 2005). In addition, supplementation of microalgae Haematococcuspluvialis as a dietary carotenoid source presented higher survival rate and weight gain of juvenile vaname shrimp (Litopenaeus vannamei) (Parisenti et al, 2011). Even though these previous studies did not provide suffi- cient data on biomass, the significant higher growth and survival detected in those studies implied a significantly higher biomass which was similar to that of found in the present study.…”
Section: Growth Survival and Biomass Production Of Shrimpsupporting
confidence: 49%
See 3 more Smart Citations
“…A similar effect was also reported on Kuruma prawn (Penaeus japonicus) fed with -carotene from Dunaliella salina (Supamattayaa et al, 2005). In addition, supplementation of microalgae Haematococcuspluvialis as a dietary carotenoid source presented higher survival rate and weight gain of juvenile vaname shrimp (Litopenaeus vannamei) (Parisenti et al, 2011). Even though these previous studies did not provide suffi- cient data on biomass, the significant higher growth and survival detected in those studies implied a significantly higher biomass which was similar to that of found in the present study.…”
Section: Growth Survival and Biomass Production Of Shrimpsupporting
confidence: 49%
“…Microalgae have been widely acknowledged to contain various carotenoids such as Haematococcus pluvialis (Parisenti et al, 2011), Botryococcus brauni (Rao et al, 2006) and Dunaliella salina (Boonyaratpalin et al, 2001). A recent study reported that Tetraselmis sp DS3 contains > 5% -carotene and 0.48% lutein of biomass and also has the same biological functions as other carotenoid sources (Tsai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…pluvialis has been shown to be successful in enhancing the reddish skin coloration of red porgy, Pagrus pagrus (Chatzifotis et al 2011) and also of the penaeid shrimp, Litopenaeus vannamei (Parisenti et al 2011). Both natural and synthetic sources of carotenoids have been successfully used to augment the yellow skin coloration in gilthead sea bream Gouveia et al 2002).…”
Section: Pigmentsmentioning
confidence: 97%